2019
DOI: 10.3389/fonc.2019.00669
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Long Non-coding RNAs, Micro-RNAs and mRNAs: Deciphering Molecular Mechanisms of Master Regulators in Cancer

Abstract: Cancer is a complex disease, and its study requires deep understanding of several biological processes and their regulation. It is an accepted fact that non-coding RNAs are vital components of the regulation and cross-talk among cancer-related signaling pathways that favor tumor aggressiveness and metastasis, such as neovascularization, angiogenesis, and vasculogenic mimicry. Both long non-coding RNAs (lncRNAs) and micro-RNAs (miRNAs) have been described as master regulators of cancer on their own; yet there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(143 citation statements)
references
References 76 publications
0
143
0
Order By: Relevance
“…Accumulative evidence reveal a clear involvement of the individual lnRNAs of the 8q24.21 gene desert in tumorigenesis (Table 1), a concept that is supported by the emerging roles of lnRNAs in tumorigenesis via complex mechanisms [44,45]. Upregulations of PRNCR1 (prostate cancer non-coding RNA1) occurred in prostate cancer (PC), and precancerous lesions PINs (prostatic intraepithelial neoplasia) and knockdown of PRNCR1 reduced the survival of PC cells and the expression of androgen receptor (AR), indicating an important role of PRNCR1 in facilitating PC via AR signaling (Table 1) [46].…”
Section: Association Of the 8q2421 Gene Desert With Oncogenesismentioning
confidence: 94%
“…Accumulative evidence reveal a clear involvement of the individual lnRNAs of the 8q24.21 gene desert in tumorigenesis (Table 1), a concept that is supported by the emerging roles of lnRNAs in tumorigenesis via complex mechanisms [44,45]. Upregulations of PRNCR1 (prostate cancer non-coding RNA1) occurred in prostate cancer (PC), and precancerous lesions PINs (prostatic intraepithelial neoplasia) and knockdown of PRNCR1 reduced the survival of PC cells and the expression of androgen receptor (AR), indicating an important role of PRNCR1 in facilitating PC via AR signaling (Table 1) [46].…”
Section: Association Of the 8q2421 Gene Desert With Oncogenesismentioning
confidence: 94%
“…Long noncoding RNAs (lncRNAs) are novel class of regulatory RNAs, which are involved in numerous biological processes via interaction with mRNAs and miRNAs, such as miRNA and lncRNA competition for the same mRNA target, and lncRNAs acting as decoys (or sponges) for miRNAs [ 154 ]. By RNA sequencing of hypertrophic and leaner broilers, Li et al identified a novel lncRNA, termed lncIRS1, is upregulated in hypertrophic muscles.…”
Section: Atrophy-related Mirs and Their Potential Regulation Of Imentioning
confidence: 99%
“…Evaluation of circulating miRNAs and lncRNAs trough liquid biopsies is appealing and has been extensively performed in a variety of cancers, where these molecules have often shown prognostic and predictive roles [45]. In PDAC, both overexpression and downregulation of specific miRNAs have been associated with poor prognosis.…”
Section: Microrna and Long Non-coding Rnamentioning
confidence: 99%